Pelatihan Pengelolaan Keuangan Keluarga bagi Anggota Kelompok Tani Nira Sari Murni - Zusak, M Bastomi Fahri; Fuadi, Ariza; Kurnia, Akhmad Syakir; Firmansyah; Sugiyanto, FX (Yayasan Sagita Akademia Maju, 2025)
Farmer groups play a strategic role in maintaining food security and the sustainability of the rural economy. One such group is the Nira Sari Murni Farmer Group, where most of its members rely on farming and coconut sap production for their income. However, the main challenge they face is suboptimal family financial management, which can impact household economic stability. The lack of expense recording, budget planning, and understanding of emergency fund management are common problems. Through this training, farmer group members are equipped with basic knowledge and skills in practical and applicable family financial management. The training covers techniques for preparing a household budget, recording daily cash flow, managing debt, and planning for short- and medium-term needs. This activity is expected to improve financial literacy and the economic resilience of farming families.